Strong $T$-Stability of Picard Iteration in a Non-Normal Cone Metric Space (Analysis in Theory and Applications, 2023)
Let $(X, d)$ be a cone metric space and $T : X → X$ be a mapping. In this paper,we shall introduce the concept of strong $T$-stability of fixed point iteration procedureswith respect to $T$ in cone metric spaces. Also, we will investigate some meaningfulresults on strong $T$-stability of Picard iterations in cone metric spaces without the assumption of normality. Our main results improve and generalize some related resultsin the literature.
Keywords: Strong $T$-stability; Picard iteration; non-normal cone; cone metric space.